ANALYSIS OF TECHNICAL AND HUMAN RESOURCES PROVISIONS FOR OPERATION OF RADIOISOTOPE DIAGNOSTIC DEPARTMENTS IN SAINT-PETERSBURG - N. M. Vishnyakova; I. K. Romanovich; L. A. Ivanova; S. A. Kalnitsky (Радиационная гигиена, 2017)
The article contains analysis of the instrument, technological and human resources provisions for radioisotope diagnostic departments. The decrease of the number of radioisotope examinations in Russia, amount of apparatus and specialists in this field of diagnostics is recorded. The operation time of the major part of apparatus is more then 20 years, this results in higher dose loads both for personnel and patients. The article demonstrates that reduction of the amount of apparatus and specialists is going with increased speed in comparison with reduction of the amount of radioisotope diagnostic examinations. This unfavorable trend creates increased workload on apparatus, and, especially, on the personnel of radioisotope diagnostic departments.